Empowerment of Farmer Groups in Rambahan Village in Processing Palm Oil Mill Waste into Organic Fertilizers for Porang (Amorphophallus muelleri) Plantation - Made Deviani Duaja; Johannes Johannes; Elis Kartika; Lizawati Lizawati (Universitas Medan Area, 2022)
Porang (Amorphophallus muelleri), also known as Iles-Iles or Suweg. In its cultivation, porang has a shade tolerance of 60 percent. But without using shade, it can still be cultivated. Farmers in Jambi usually planted porang among old rubber plants without fertilizing. This causes porang tuber production to be at a minimum below its potential. Porang is only produced without treatment, reducing the size of the tubers, and the konjac glucomannan content in tubers is low. Porang tubers are usually made into chips, and chips will crumble easily if the konjac glucomannan is low. Based on this, counseling and mentoring activities will focus on making fertilizer from the waste from palm oil mills. Palm oil mill waste that is most easily transported and easily decomposed is the cake decanter (DC). In the village of Rambahan, it is known as a solid decanter. The village community had heard but did not know that this waste with specific treatments could be used as organic fertilizer. That this waste, with particular treatments, can be used as organic fertilizer. The treatment is by fermentation with local microorganisms (LOM) from cow urine mixed with MOL from snails (RINMAS). Keongmas are pests and are widely found in farmers' fields. Beef and conch urine are used as LOM. After they are made, the two LOMs are mixed with a ratio of 1: 1 and used as a decomposer to ferment the decanter cake plus for two months. After two months, it can be used as organic fertilizer for porang plants. LOM cow urine and LOM snail (RINMAS) are also used as foliar fertilizers. The technology application activities will be carried out in Rambahan Village at the Mekar Kembali KT and KWT Pokja Alamanda. The target for KT Mekar Kembali and KWT Pokja Alamanda is to increase the area of porang plants, which previously were only intercrops, now every KT, there is an increase in the area of porang plants every KT of 0.5 hectares. Once, farmers and KWT did not know how to make solid and liquid fertilizers. After counseling and DEMPLOT, they could make their fertilizers. Every two months, the farmers produce 100 kg of solid fertilizer decanter cake, urine MOL, and Keongmas MOL as 100 liters of liquid fertilizer per month.